Papular mucinosis (papular lichen myxedematosus): Clinical and histopathological evaluation - Khalifa Sharquie; Raed I Jabbar (Our Dermatology Online, 2021)
Background: Papular mucinosis is a variety of mucinosis characterized by excessive production of mucin by fibroblasts and deposition in the dermis. It manifests itself with fleshy papules or plaques in different sites of the body and taking different clinical morphological cutaneous features. Objective: The objective is to report and evaluate the different clinical and histopathological features of the disease in Iraqi patients. Patients and Methods: This is a case series and a clinical descriptive study in which ten patients with papular mucinosis were reported during the period from 2012 through 2019. The age ranged from 4 to 56 years, with seven females and three males. Clinical evaluation regarding histories of the disease and examination was carried out. General investigation was done and skin biopsy for histopathological assessment was conducted. Results: Nine patients were adults, with their age ranging from 20 to 56 years, a mean of around 35 years, and only one 4-year-old child. It is a disease with a female predominance, as observed in 7 (70%) females. The common sites of involvement were the face but the rash may extend to affect the neck and upper arms. The rash appeared in the form of skin-colored or red fleshy papules and plaques or in diffuse erythematous orange peel-like forms. The rash was asymptomatic in most patients. The pathology of the disease clarified the diffuse deposition of mucin in the dermis, as was demonstrated with H&E staining. Conclusion: Papular mucinosis is a rare disease characterized by mucin deposition in the skin affecting mostly adult females. The face is commonly involved together with other areas such as the neck and upper arms, but the trunk and lower limbs are spared. It manifests itself with different clinical morphological cutaneous features. Papular granuloma annulare must be considered as an important differential diagnosis in all cases of papular mucinosis.